Family Health Exercise: Follow-up of an Extra-pulmonary Tuberculosis Patient - Thapa, Kavindra; Sharma, D; Karki, D; Sharma, D; Gurung, FK; Tanwar, J; Pariyar, L (Journal of Gandaki Medical College-Nepal, 2017)
During the third year of MBBS program, we had a course of family health exercise in community medicine. This course was designed to produce competent family physicians; to enable us to understand the social, cultural, psychological, gender and economical aspects of illness, the interactions of ill persons with different members of the family and community health service, role of family members and family environment in patient care. It helped us to understand the natural history of the disease and importance of patient follow up. We were able to differentiate the nature of the problems while seeing the patients in the family from the nature of the same problems when the patient is seen in clinic or hospital. Here we present a follow-up of extra-pulmonary tuberculosis patient in our family health exercise during third year MBBS program. Journal of Gandaki Medical College Volume, 09, Number 2, July December 2016, Page: 70-75